Bilateral Anomalous Pulmonary Venous Connection to Bilateral Superior Caval Veins. (January 2014) - Sasikumar, Navaneetha; Ramanan, Sowmya; Chidambaram, Shanthi; Rema, Krishna Manohar Soman; Cherian, Kootturathu Mammen
A four-year-old girl presented with superior vena cava (SVC) type of sinus venosus defect, right upper pulmonary vein draining into right SVC-right atrium junction, left upper lobe pulmonary veins draining into the lower part of persistent left SVC (LSVC), and a patent ductus arteriosus. The anomalous pulmonary venous drainage to LSVC was overlooked in the preoperative evaluation and was found intraoperatively. Warden procedure was performed for right-sided veins. Lower LSVC draining the anomalous pulmonary veins was anastomosed to the left atrial appendage. The short stump of LSVC was diverted to left pulmonary artery. Anomalous pulmonary venous connections to LSVC are rare. Embryology of venous development is analyzed with respect to this rare anomaly, and options for surgical correction are discussed.